Analysis of the Availability and Gaps of Educational Facilities in Teluk Bintuni Regency Papua - Ibrahim, Riza Adrian; Sidiq, Fahmi; Vaidyanatahan, Sundarapandian (International Journal of Ethno-Sciences and Education Research, 2024)
Education is recognized as a human right and the main key to a nation's progress. The availability of adequate educational facilities in each region is crucial to ensure equal access to education for all citizens. However, Indonesia faces significant challenges in providing equitable educational facilities, especially considering the diverse geographical and demographic conditions between regions. Teluk Bintuni Regency in West Papua Province is one of the areas that requires special attention in improving educational access and facilities, especially because of its geographical conditions, the majority of which are islands with mountains and sea waters. This research aims to analyze the availability of educational facilities in Teluk Bintuni Regency, with a focus on the type and level of schools. Data obtained from the Education Department shows that by 2023, this district will only have 263 schools, consisting of kindergartens, elementary schools, middle schools, high schools and vocational schools. This figure is still considered insufficient and equitable, especially when compared with the population of around 60,000 people spread across 23 sub-districts. The main challenge in providing equitable educational facilities in Teluk Bintuni Regency involves diverse geographic and demographic conditions. Therefore, it is hoped that this research can provide an in-depth evaluation of the current condition of educational facilities, identify existing gaps, and formulate the need for improving educational facilities in the future based on population growth projections. It is hoped that the results of this research can provide a strong basis for policy making by the Teluk Bintuni Regency Government, especially in terms of planning and budgeting for the equitable development of educational facilities. It is also hoped that the conclusions from this research can become a reference for related agencies, such as the Education Office, Bappeda, and the Teluk Bintuni Regency DPRD, in preparing strategic plans for educational development for the next five years.